2020
DOI: 10.3390/molecules25143209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gelatine Packaging Film Containing a Spirulina platensis Protein Concentrate on Atlantic Mackerel Shelf Life

Abstract: The use of packaging films containing natural preservative compounds attracts great attention for the quality improvement of seafood. Microalga spirulina (Spirulina platensis) represents a potential source of high added-value and preservative biocompounds. The goal of this study was to enhance the quality of refrigerated Atlantic mackerel (Scomber scombrus) by including a protein concentrate (PC) of spirulina in a gelatine-based film. Quality changes in fish muscle were monitored by microbial and chemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Glazing techniques by water (fortified or nonfortified with antioxidants, cryoprotectant, etc. ), chitosan, or liquid coating with plant extracts (e.g., seaweed extracts and essential oils) are effective as well (Noordin et al., 2014; Rodriguez et al., 2011; Sathivel et al., 2007; Sawant, 2012; Shi et al, 2019; Stejskal et al., 2020; Wang et al., 2016). Based on the available literature, to minimize damages in frozen fish over greater extended frozen storage (9–12 months), using fortified glazing combined with protective‐film vacuum or tight packaging may be the best “hurdle‐system” (Hao et al., 2021).…”
Section: Results Of Literature Review and Metadata Analysesmentioning
confidence: 99%
“…Glazing techniques by water (fortified or nonfortified with antioxidants, cryoprotectant, etc. ), chitosan, or liquid coating with plant extracts (e.g., seaweed extracts and essential oils) are effective as well (Noordin et al., 2014; Rodriguez et al., 2011; Sathivel et al., 2007; Sawant, 2012; Shi et al, 2019; Stejskal et al., 2020; Wang et al., 2016). Based on the available literature, to minimize damages in frozen fish over greater extended frozen storage (9–12 months), using fortified glazing combined with protective‐film vacuum or tight packaging may be the best “hurdle‐system” (Hao et al., 2021).…”
Section: Results Of Literature Review and Metadata Analysesmentioning
confidence: 99%
“…For instance, microalgal compounds have shown antimicrobial effects against some sh pathogenic bacteria both in vitro (Narasimhan et al, 2013) and in vivo (Magnoni et al, 2017). This potential of algal extracts might well be contemplated as natural additive for external application when it comes to preserving fresh sh, and thus, several studies have reported delayed growth of spoilage bacteria during cold storage of sh, this ending up in increased sh shelf life (Yarnpakdee et al, 2019;Stejskal et al, 2020;Sáez et al, 2021). In addition to the value of algal extracts as food additive intended for direct application on sh, they have also been proposed as feed additives, with the aim of improving different physiological aspects of live sh.…”
Section: ; Saez Et Al 2022a)mentioning
confidence: 99%
“…Concerning microalgae, the presence of a protein concentrate from Spirulina platensis in the gelatin packing film led to higher PUFA retention in refrigerated (4 °C) hake ( M. merluccius ) muscle [ 16 ]. A lower content of fluorescent compounds was obtained in mackerel ( S. scombrus ) muscle packed in a gelatin film containing a protein concentrate from S. platensis during storage at 4 °C [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning microalga employment, S. platensis extracts, including polyhydroxybutyrate and phenolic compounds, allowed active packing strategies due to their antimicrobial activity when included in edible films [ 61 ]. Moreover, active films have also been prepared by including a protein concentrate from S. platensis in a gelatin film, leading to better microbial growth in refrigerated hake ( M. merluccius ) [ 16 ] and mackerel ( S. scombrus ) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%